2006
DOI: 10.1111/j.1600-0846.2006.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine ear skin: an in vitro model for human skin

Abstract: The results obtained are similar to those of human skin, indicating the suitability of this porcine tissue as a model for human skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
242
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(266 citation statements)
references
References 23 publications
6
242
2
6
Order By: Relevance
“…In previous years our groups was able to establish an excellent correlation regarding the amount of hair follicles available, as well as the quantitative follicular uptake of nanoparticles between pig ear tissue in vitro and human forearm skin in vivo [29]. However, it is noteworthy that the amount of terminal hairs available for this type of therapy on the average human scalp is much higher than what is seen on porcine ear skin (124-200 hairs per cm 2 on human occipital scalp vs. 11-25 cm 2 on porcine ear skin) [43][44][45]. Therefore, an even higher follicular recovery and potential for a depot effect on the scalp is to be expected in vivo, only further corroborating the potential of this type of application for the above mentioned conditions.…”
Section: Potential Of Nanocarriers From a Clinical Perspectivementioning
confidence: 99%
“…In previous years our groups was able to establish an excellent correlation regarding the amount of hair follicles available, as well as the quantitative follicular uptake of nanoparticles between pig ear tissue in vitro and human forearm skin in vivo [29]. However, it is noteworthy that the amount of terminal hairs available for this type of therapy on the average human scalp is much higher than what is seen on porcine ear skin (124-200 hairs per cm 2 on human occipital scalp vs. 11-25 cm 2 on porcine ear skin) [43][44][45]. Therefore, an even higher follicular recovery and potential for a depot effect on the scalp is to be expected in vivo, only further corroborating the potential of this type of application for the above mentioned conditions.…”
Section: Potential Of Nanocarriers From a Clinical Perspectivementioning
confidence: 99%
“…It was previously shown that pig ear skin is a suitable model for human skin in penetration studies [19,20]. Each ear was washed and shaved under cold water and wiped dry with soft tissue.…”
Section: Measurements On Pig Ear Skinmentioning
confidence: 99%
“…The SC thickness of three skin models had been measured, the SC thickness of pig abdominal skin, pig ear skin and hairless mouse skin were approximately 25, 23 and 14 mm, respectively, which was corresponding to the data reported in the references. Studies examining thickness of various skin layers of pigs have shown that the SC thickness of pig abdominal skin was 21-26 mm which was comparable to pig ear skin (17-28 mm) (Jacobi et al, 2007). The SC thickness of pig skin was comparable with human skin (about 30 mm verified by various studies), while the SC thickness of hairless mouse skin was only half of human.…”
Section: The Role Of Sc On Percutaneous Penetration Of Mtzmentioning
confidence: 68%
“…Histological and biochemical properties of porcine skin have been repeatedly shown to be similar to human skin. The thickness of viable skin layers, numbers of hairs, the vascular anatomy and collagen fiber arrangement in the dermis, as well as the contents of SC glycosphingolipids and ceramides were similar in man and in the domestic pig (Wester & Maibach, 1989;Simon & Maibach, 2000;Jacobi et al, 2007). Due to its availability, skin of rodents was the most commonly used in in vitro and in vivo percutaneous permeation studies (Godin & Touitou, 2007).…”
Section: Introductionmentioning
confidence: 99%